2021
DOI: 10.1017/cjn.2021.184
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Stop Signal Reaction Times in Alzheimer’s and Parkinson’s Disease

Abstract: Background: To investigate the relative contributions of cerebral cortex and basal ganglia to movement stopping, we tested the optimum combination Stop Signal Reaction Time (ocSSRT) and median visual reaction time (RT) in patients with Alzheimer’s disease (AD) and Parkinson’s disease (PD) and compared values with data from healthy controls. Methods: Thirty-five PD patients, 22 AD patients, and 29 healthy controls were recruited to this study. RT and ocSSRT were measured using a hand-held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Several studies found that people with Parkinson’s disease needed more time to perform reaction time tests compared to healthy controls [ 93 , 94 ]. Furthermore, Morrison et al, with a similar reaction test for upper and lower limbs, found a correlation between the risk of falling and slowing reaction time in Parkinson’s disease [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that people with Parkinson’s disease needed more time to perform reaction time tests compared to healthy controls [ 93 , 94 ]. Furthermore, Morrison et al, with a similar reaction test for upper and lower limbs, found a correlation between the risk of falling and slowing reaction time in Parkinson’s disease [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of any within-individual changes to SSRT across sessions is also potentially relevant in a clinical context. SSRT is sensitive to cortical and basal ganglia impairments resulting from healthy aging (Bloemendaal et al 2016 ; Coxon et al 2016 , 2012 ) and a wide range of pathologies such as PD (Gauggel et al 2004 ; Obeso et al 2011 ; Rahman et al 2021 ), schizophrenia (Hughes et al 2012 ), ADHD (Lipszyc and Schachar 2010 ; Senderecka et al 2012 ) and OCD (Lipszyc and Schachar 2010 ; McLaughlin et al 2016 ). It has been suggested that SSRT is a biomarker for specific pathologies and may hold promise for early diagnosis of cortical/basal ganglia dysfunction (McLaughlin et al 2016 ; Rahman et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…SSRT is sensitive to cortical and basal ganglia impairments resulting from healthy aging (Bloemendaal et al 2016 ; Coxon et al 2016 , 2012 ) and a wide range of pathologies such as PD (Gauggel et al 2004 ; Obeso et al 2011 ; Rahman et al 2021 ), schizophrenia (Hughes et al 2012 ), ADHD (Lipszyc and Schachar 2010 ; Senderecka et al 2012 ) and OCD (Lipszyc and Schachar 2010 ; McLaughlin et al 2016 ). It has been suggested that SSRT is a biomarker for specific pathologies and may hold promise for early diagnosis of cortical/basal ganglia dysfunction (McLaughlin et al 2016 ; Rahman et al 2021 ). However, to identify any impairments in inhibitory control over time because of pathology, natural trends in the SSRT measure over time need to be quantified first in healthy populations.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of any within-individual changes to SSRT across sessions is also potentially relevant in a clinical context. SSRT is sensitive to cortical and basal ganglia impairments resulting from healthy aging (Coxon et al, 2012; Bloemendaal et al, 2016; Coxon et al, 2016) and a wide range of pathologies such as PD (Gauggel et al, 2004; Obeso et al, 2011; Rahman et al, 2021), schizophrenia (Hughes et al, 2012), ADHD (Lipszyc and Schachar, 2010; Senderecka et al, 2012) and OCD (Lipszyc and Schachar, 2010; McLaughlin et al, 2016). It has been suggested that SSRT is a biomarker for specific pathologies and may hold promise for early diagnosis of cortical/basal ganglia dysfunction (McLaughlin et al, 2016; Rahman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…SSRT is sensitive to cortical and basal ganglia impairments resulting from healthy aging (Coxon et al, 2012; Bloemendaal et al, 2016; Coxon et al, 2016) and a wide range of pathologies such as PD (Gauggel et al, 2004; Obeso et al, 2011; Rahman et al, 2021), schizophrenia (Hughes et al, 2012), ADHD (Lipszyc and Schachar, 2010; Senderecka et al, 2012) and OCD (Lipszyc and Schachar, 2010; McLaughlin et al, 2016). It has been suggested that SSRT is a biomarker for specific pathologies and may hold promise for early diagnosis of cortical/basal ganglia dysfunction (McLaughlin et al, 2016; Rahman et al, 2021). However, to identify any impairments in inhibitory control over time because of pathology, natural trends in the SSRT measure over time need to be quantified first in healthy populations.…”
Section: Discussionmentioning
confidence: 99%